Organizational commitment and job quitting among staff in Administrative chancellery of Isfahan University of Medical Sciences - L. Vali; A. Hassanzadeh; M. Khamesipoor; H. Sajadi (Salāmat-i kār-i Īrān, 2009)
Background and aimsOrganizational commitment has left a considerable impact on work output of employees as well as on many of their behaviors. On one side one of the issues affecting job behavior of employees and has increasingly become problematic for organizations is Job quitting. This study aimed to survey the Organizational commitment and Job quitting at IsfahanUniversity of Medical Sciences.MethodsThis cross-sectional study was carried out in 2008. The staffs of Administrative Vice-Chancellery of Isfahan University of medical sciences were our statistical population. Data were collected by questionnaire that its validity and reliability was tested in past studies. Date was analyzed by SPSS software.ResultsThe score of organizational commitment was gained 58.45. The score of affective commitment was 63.27 (first rank), continuance commitment was 50.28 (third rank) and normative commitment was 60.33 (second rank). The maximum score was 100. Furthermore job quitting was in low level.ConclusionProviding more job security, reforming the employment systems, job enrichment, making some positive changes in organizational culture, holding appropriate training and socializing courses, skill development programs and providing more facilities for staffs are useful to increase commitment and decrease Job Quitting.